Explicație pas cu pas:
[tex]{\left( \sqrt{y} + \frac{1}{ \sqrt{x} } \right)}^{400} = {\left( {y}^{ \frac{1}{2} } + {x}^{ - \frac{1}{2}} \right)}^{400} \\ [/tex]
[tex]T_{k+1} = C_{n}^{k}\cdot a^{n-k}\cdot b^{k} \\ [/tex]
=>
[tex]T_{k+1} = C_{400}^{k}\cdot \left( {y}^{ \frac{1}{2} } \right)^{400-k}\cdot \left( {x}^{- \frac{1}{2} } \right)^{k} \\ [/tex]
[tex]\iff T_{k+1} = C_{400}^{k}\cdot {y}^{ \frac{400 - k}{2} }\cdot {x}^{- \frac{k}{2} } \\[/tex]
termenul care nu îl conține pe y din această dezvoltare: îl conține pe y⁰
[tex] \frac{400 - k}{2} = 0 \iff 400 - k = 0 \implies k = 400 \\ [/tex]
=>
[tex]T_{400+1} = C_{400}^{400}\cdot {y}^{ \frac{400 - 400}{2} }\cdot {x}^{- \frac{400}{2} }\\ \iff T_{401} = {x}^{-200 }[/tex]